Application of the 汉语的语义学 [Hànyǔ de Yǔyì Xué] (Chinese Semantic) Digital Module in Semantic Courses of Mandarin Education Program of State University of Malang - Karina Fefi Laksana Sakti; Amira Eza Febrian Putri; Octi Rjeky Mardasari; Sunarti Sunarti (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
The aims of this study are: (1) to describe the application of the 汉语的语义学[Hànyǔ de Yǔyì Xué] (Chinese semantic) digital module in the semantic course of the Mandarin Language Education Study Program, State University of Malang, and (2) to describe student responses to the 汉语的语义学Chinese semantics digital module. This study used descriptive qualitative method. The data sources used in this study were students of class 2020 B of the Mandarin Language Education Study Program, State University of Malang. The data from this study were obtained from the results of observations and the results of student response questionnaires. The results of observations from this study indicate that learning activities by applying the 汉语的语义学 [Hànyǔ de Yǔyì Xué] (Chinese semantic) digital module run smoothly. Students of 2020 B enthusiastically participated in all learning activities in semantic courses from beginning to end. In addition, students can also understand Chinese semantic material easily, as evidenced by students being able to complete the practice questions in the module well. Based on the results of the student response questionnaire, it can be seen that the 汉语的语义学 [Hànyǔ de Yǔyì Xué] (Chinese semantic) digital module makes students easier to learn Chinese semantic material anywhere and anytime. Students can understand Chinese semantic material quickly, because the material in this 汉语的语义学 [Hànyǔ de Yǔyì Xué] (Chinese semantic) digital module is written in Indonesian. It can be concluded that the 汉语的语义学Chinese semantic digital module is effective to be applied to the semantic course of the Mandarin Language Education Study Program, State University of Malang.